Papillary Muscles of the Left Ventricle: Integrating Electrical and Mechanical Dynamics - Csilla Andrea Eötvös; Teodora Avram; Roxana Daiana Lazar; Iulia Georgiana Zehan; Madalina Patricia Moldovan; Patricia Schiop-Tentea; Giorgia Coseriu; Adriana Sarb; Gabriel Gusetu; Elena Buzdugan; Roxana Chiorescu; Diana Mocan-Hognogi; et al. (Journal of Cardiovascular Development and Disease)
Background: Papillary muscles are structures integrated into the mitral valve apparatus, having both electrical and mechanical roles. The importance of the papillary muscles (PM) is mainly related to cardiac arrhythmias and mitral regurgitation. The aim of this review is to offer an overview of the anatomy and physiology of the papillary muscles, along with their involvement in cardiovascular pathologies, including arrhythmia development in various conditions and their contribution to secondary mitral regurgitation. Methods: A literature search was performed on PubMed using the following relevant keywords: papillary muscles, mitral valve, arrhythmia, anatomy, and physiology. Results: During the cardiac cycle, papillary muscles have continuous dimensional and pressure changes. On one hand, their synchrony or dyssynchrony impacts the process of mitral valve opening and closure, and on the other hand, the pressure changes can trigger electrical instability. There is increased awareness of papillary muscles as an arrhythmic source. Arrhythmias arising from PM were found in patients with or without structural heart disease, via Purkinje fibres, due to increased automaticity or triggered activity. Conclusions: Despite the interest in mitral valve physiology, there are still many unknowns in relation to the papillary muscles, especially with regard to their role in arrhythmogenesis and the pathogenesis of mitral regurgitation.